Prolonged effects of adenoviral vector priming on T-cell cytokine production in heterologous adenoviral vector/mRNA COVID-19 vaccination regimens - Masanori Isogawa; Taishi Onodera; Akira Ainai; Ryutaro Kotaki; Takayuki Kanno; Shinji Saito; Minoru Tobiume; Kenzo Tokunaga; Megumi Hara; Yoshio Hirota; Tadaki Suzuki; Yoshimasa Takahashi; et al. (Scientific Reports)
Abstract mRNA and adenoviral vector vaccine platforms were used for the primary series of COVID-19 vaccines in many countries. However, the distinct immunogenic properties on these platforms remain less understood. We traced neutralizing antibodies, memory B cells, and T cells longitudinally in cohorts that received either mRNA (BNT162b2 or mRNA-1273) or adenoviral vector (ChAdOx1) vaccines with homologous or heterologous regimens (total 9 groups, n = 26–28 for each group) at 4 weeks interval. The priming and boosting effects on various immune parameters were comparably assessed between mRNA and adenoviral vector platforms. We found that initial priming by adenoviral vector vaccine elicited robust T cell responses, but B cell responses, including antibody titers, were relatively lower than those elicited by mRNA priming. The dissociation between T cell and antibody responses were exaggerated at greater extents after the homologous booster with the adenoviral vector vaccine, resulting in 5-19-fold lower antibody titers despite comparable spike-specific T cell numbers at day 28 after the boost. Robust IFN-γ and few IL-2 and IL-5 production characterized T cell functionality primed by adenoviral vector. Boosting with mRNA vaccines restored their IL-2 and IL-5 production at some extents, but the IL-5 T cell responses elicited by adenoviral vector/mRNA heterologous regimen waned faster than those by mRNA homologous regimen. Thus, our data revealed that the cytokine production of helper T cells was skewed by adenoviral vector priming, leading to the attenuated IL-2 and IL-5 responses which were prolonged even after mRNA boosting, suggesting an imprinting of T-cell functionality depending on the vaccine platform used for initial priming. These results highlight the importance of selecting vaccine platforms based on the immunogenic properties.